Dentist's preferences on vital and nonvital tooth bleaching - Víctor Ernesto Villagrán Colón; Mirna Oldemia Calderón Márquez; Ricardo Alfredo Carrillo-Cotto; Flavio Fernando Demarco; Luiz Alexandre Chisini (Universidade Estadual de Campinas, 2021)
Aim: The present study aimed to investigate if the Guatemalan dentist's options on tooth bleaching could be influenced by their time in clinical practice, the level of specialization or their working place. Methods: A representative sample of dentists working in clinical practice in Guatemala was selected. Data were collected using a self-administered questionnaire with information related to gender, professional characteristics (time since graduation in years and working place) and preferences regarding vital (at-home or in-office; type and concentration of bleaching agent) and the nonvital tooth bleaching (bleaching agent used). The analysis was performed and the association between preference for bleaching technique and independent variables were investigated using Fisher's exact test. Results: 200 dentists were interviewed. More than half of dentists were male (57.0%) with time since graduation between 11 and 20 years (n= 64; 32.3%). Dentists mostly (60.5%) preferred in-office technique for vital bleaching, with 10-20% Carbamide peroxide (CP) as the preferred agent (50%). For nonvital teeth, the preferred agent (46.8%) was 37% Hydrogen Peroxide (HP). About the associations, younger dentists (< 20 years of graduation) selected mostly in-office technique, while those with more than 20 years indicated more the at-home technique. Also, the dentists working in private practice chose more frequently in-office technique. Thus, the in-office technique was more popular among Guatemalan dentists, with 10-20% CP and 37% HP selected as favorite bleaching agents for vital and nonvital techniques, respectively. Conclusion: The time of clinical practice and working place influenced some choices.